PENERAPAN METODE K-MEANS UNTUK PENGELOMPOKAN DATA KAPAL BARANG (STUDI KASUS: KSOP PEKANBARU) - Ariq At-Thariq Putra; Alwis Nazir; Febi Yanto; Suwanto Sanjaya; Fadhilah Syafria (SYNTAX Jurnal Informatika, 2023)
Transportation by sea is crucial for national development as it contributes to the growth of the economy and other ship transport sectors. With the increasing demand for cargo ships in the maritime transportation industry, data clustering is needed to review the growth of cargo ships in Riau. K-Means is a commonly used technique for clustering data that helps to classify data effectively. This algorithm is not influenced by data series and starts with the random determination of cluster centers during calculation. This cargo ship research aims to classify cargo ship data at the Pekanbaru KSOP, which allows the Pekanbaru KSOP to easily monitor the development of cargo ships.